Effect of resveratrol on diabetic neuropathy in wistar albino rats - Das, Smita; Behera, Jayanti Prava; Rojaramani, Y.; Mohanty, Rashmi Ranjan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Type 2 diabetes mellitus (DM) is a common chronic disease with increasing prevalence worldwide. Prolonged uncontrolled hyperglycemia, dyslipidemia are major risk factor for its complication like neuropathy. Since there is no definite treatment for diabetic neuropathy, this study aims to evaluate the effect of resveratrol on diabetic neuropathy in high fat diet with low dose streptozotocin induced type-2 DM model in wistar albino rats. Methods: First type 2 diabetic rat model was established. Wistar albino rats, fed with high-fat diet (HFD) rendered diabetic with streptozotocin, were divided into 6 groups, disease control (DC) treated with vehicle, standard control (SC) which received metformin, test groups treated with 5, 10, and 20 mg/kg b.w. of resveratrol and combination of half dose of metformin and resveratrol (10 mg/kg) (TC). A group of six normal animals served as normal control (NC), another six as HFD control. Fasting plasma glucose, lipid profile were measured one week after induction of diabetes. The animals were then treated orally for 2 weeks after which the same parameters were repeated. Behavioral biomarkers for neuropathy are measured in 4 weeks and 6 weeks of treatment. The in-vivo results were analyzed by one way ANOVA followed by Tukey’s multiple comparison test for biochemical parameters and Kruskal Wallis test followed by Dun’s multiple comparison test for behavioral biomarkers. Results: Increase in fasting plasma glucose (FPG), deranged lipid profile, increased neuropathy in DC compared to NC, HFD control while a significant decrease in FBG, improved pain behavior with SC, test groups (p<0.05) as compared to the DC group. Conclusions: Resveratrol prevents diabetic neuropathy.